Occurrence of fruit rot on cornelian cherry caused by Pilidium lythri in Iran. (November 2019) - Torbati, Mohsen; Arzanlou, Mahdi; Abed-Ashtiani, Farnaz; Golmohammadi, Hadi
Abstract: Cornus mas (Cornelian cherry or European cornel) is a deciduous shrub with edible fruits that have medicinal benefits and is native to southern Europe and south-western Asia. This shrub grows wild in Arasbaran forests and the Qazvin region in Iran. In this study a new fruit rot disease was discovered on cornelian cherries in Arasbaran forests located in the north-west zone of Iran. Fruit samples were collected from severely infected C. mas trees in October 2017. Ten fungal isolates with the same morphological characteristics were recovered from symptomatic tissues on potato dextrose agar culture medium. The causal agent of the disease was identified as Pilidium lythri based on macro and micro morphological and molecular characterizations. In addition, random amplified polymorphic DNA (RAPD) and inter-simple sequence repeat (ISSR) fingerprintings were used to assess five P. lythri isolates (one isolate from each five parts of the forest) from cornelian cherry, five isolates from strawberry, and two isolates from olive. Based on the results, no polymorphism was observed among the isolates, denoting limited genetic variability. Pathogenicity assays confirmed P. lythri isolates to be pathogenic on cornelian cherry and strawberry fruits in vitro condition, irrespective of their origin. Based on the data presented in the current study, P. lythri isolates from different hosts showed a homogeneous genetic structure with no host preference. This is the first occurrence of P. lythri causing fruit rot on cornelian cherry in Iran and the world. Highlights: A new rot disease was observed on cornelian cherries in north-west zone of Iran. The causal agent of the disease was identified as Pilidium lythri. This is the first report of cornelian cherry rot caused by P. lythri worldwide.